DESIGNING PARTY DRESS WITH WIJAYAKUSUMA BATIK MOTIF - Siti Nafisah; Sri Marwati (ARTISTIC : International Journal of Creation and Innovation, 2022)
Wijayakusuma flower is a unique and rare flower that only blooms once at night and after that it will wither and not bloom again. This uniqueness is an attraction to make it an inspiration for batik art work. The formulation of the studdy in this creation is how to visualize the Wijayakusuma flower in the form of a batik motif and implement it into party dresses. This artistic research uses three stages, namely exploration, design and visualization. The results of this study are the creation of the Wijayakusuma batik motif, the application of the Wijayakusuma floral batik motif to the party dresses, and the realization of the Wijayakusuma batik patterned party dress. The works of this party dress are entitled Selene, Amaris, Luna, and Neoma.